2019
DOI: 10.1155/2019/1906814
|View full text |Cite
|
Sign up to set email alerts
|

Early Real-World Experience with CoreValve Evolut PRO and R Systems for Transcatheter Aortic Valve Replacement

Abstract: Objectives. The purpose of this study was to compare the efficacy and safety of the Evolut PRO to the Evolut R valve in a real-world setting. Background. The next-generation self-expanding transcatheter aortic valve replacement (TAVR) system, the CoreValve Evolut PRO was designed with an outer pericardial skirt to improve valve-sealing performance. Safety and efficacy of this valve have not previously been compared to its predecessor, the Evolut R valve. Methods. We retrospectively studied 134 patients who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 23 publications
(26 reference statements)
4
18
1
Order By: Relevance
“…29 In that study, a potentially protective effect of PMI however, there were no differences in all-cause and cardiovascular mortalities between those with and without PMI. 21 In contrast, a negative clinical impact was reported in a cohort of 9,785 patients who underwent TAVI. 58 PMI was required in 6.7% after TAVI…”
Section: Clinical Outcomesmentioning
confidence: 98%
See 1 more Smart Citation
“…29 In that study, a potentially protective effect of PMI however, there were no differences in all-cause and cardiovascular mortalities between those with and without PMI. 21 In contrast, a negative clinical impact was reported in a cohort of 9,785 patients who underwent TAVI. 58 PMI was required in 6.7% after TAVI…”
Section: Clinical Outcomesmentioning
confidence: 98%
“…2,4,[16][17][18][19] The incidence of new-onset LBBB appears to be more frequent for some self-expandable newer-generation devices, such as the Evolut R/ PRO (Medtronic; 44%) and Lotus (Boston Scientific; 74%). [20][21][22]…”
Section: New-onset Left Bundle Branch Block After Transcatheter Aortimentioning
confidence: 99%
“…These data have demonstrated that self-expanding valves are superior to balloon-expandable valves in terms of pacemaker rates and PVR for small annuli [29]. However, mortality outcomes have been equivocal, and these data are likely obsolete with newer designs aimed at reducing such complications [3,29,30] (Fig. 1 [23, 28, 31]).…”
Section: Available Transcatheter Aortic Valvesmentioning
confidence: 99%
“…The limited data available for the SAPIEN 3 Ultra show a moderate paravalvular regurgitation rate of 1.4%, with no cases of severe paravalvular regurgitation [36]. No outcome data are available at this time for the Evolut Pro?, but paravalvular regurgitation rates for its predecessor, the Evolut Pro, have been reported as low as 5% [30]. One-year follow-up data from the Lotus system showed no severe perivalvular regurgitation and only 0.4% of patients exhibiting moderate perivalvular regurgitation [37].…”
Section: Device Complicationsmentioning
confidence: 99%
See 1 more Smart Citation